Atomoxetine-related bruxism in a 7-year-old boy: A case report - Bilac, Oznur; Percinel, Ipek; Kavurma, Canem (Wolters Kluwer Medknow Publications, 2020)
[Abstract Not Available]
Keywords: Deficit Hyperactivity Disorder; Sleep Bruxism; Children